2017
DOI: 10.1111/imr.12552
|View full text |Cite
|
Sign up to set email alerts
|

IL‐33: biological properties, functions, and roles in airway disease

Abstract: Summary Interleukin (IL)-33 is a key cytokine involved in type 2 immunity and allergic airway diseases. Abundantly expressed in lung epithelial cells, IL-33 plays critical roles in both innate and adaptive immune responses in mucosal organs. In innate immunity, IL-33 and group 2 innate lymphoid cells (ILC2s) provide an essential axis for rapid immune responses and tissue homeostasis. In adaptive immunity, IL-33 interacts with dendritic cells, Th2 cells, follicular T cells, and regulatory T cells, where IL-33 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
214
1
15

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(233 citation statements)
references
References 157 publications
(456 reference statements)
3
214
1
15
Order By: Relevance
“…(A) C57BL/6J mice were intranasally exposed to saline (white bars), 25 μg DEP (striped bars), 1 μg HDM (checked bars) or combined DEP+HDM (black bars) on days 1, 8 and 15. Although under inflammatory conditions IL-33 can be induced in immune cells,8 we identified nonhematopoietic cells as the major IL-33 producers in our model of DEP-enhanced allergic airway inflammation, whereas ST2 was predominantly expressed on the hematopoietic cells. (B, C), IL-33 (B) and ST2 (C) mRNA expression in total lung tissue was determined using qRT-PCR.…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…(A) C57BL/6J mice were intranasally exposed to saline (white bars), 25 μg DEP (striped bars), 1 μg HDM (checked bars) or combined DEP+HDM (black bars) on days 1, 8 and 15. Although under inflammatory conditions IL-33 can be induced in immune cells,8 we identified nonhematopoietic cells as the major IL-33 producers in our model of DEP-enhanced allergic airway inflammation, whereas ST2 was predominantly expressed on the hematopoietic cells. (B, C), IL-33 (B) and ST2 (C) mRNA expression in total lung tissue was determined using qRT-PCR.…”
mentioning
confidence: 79%
“…3 The best characterized phenotype is allergic asthma, a type 2-mediated immune disorder caused by exposure to common inhaled allergens, such as house dust mite (HDM). [7][8][9] Several genome-wide association studies have shown that IL-33 and its receptor ST2 are associated with asthma susceptibility. It acts not only as a passive barrier but is also actively involved in respiratory defence through pro-inflammatory cytokine production.…”
mentioning
confidence: 99%
“…Chronic inflammation and tumors are closely related [25]. Inflammatory factors are an important feature of the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies have confirmed that the presence of VM can compensate for endothelium-dependent blood vessels to provide nutrients to tumors to promote tumor progression [25, 26]. At the same time, it is also the reason why the angiogenesis inhibitor trials have been disappointing in treating tumors.…”
Section: Introductionmentioning
confidence: 99%
“…IL-33 is important in the innate and adaptive immune response in the mucosal organs for chronic airway inflammation and tissue remodeling [54]. In innate immunity, IL-33 activates eosinophils, basophils, mast cells, and ILC2.…”
Section: Interleukinsmentioning
confidence: 99%